Medley spectrometer for light ions in neutron-induced reactions at 175 MeV - Bevilacqua R. (2017)
We have upgraded the Medley spectrometer to measure neutron-induced double differential cross-sections for light-ion production, with neutron energies up to 175 MeV. Measurements were performed at the quasi-monoenergetic neutron beam line at the The Svedberg Laboratory, in Uppsala (Sweden). Medley is a spectrometer system composed of eight three-element telescope detectors; ΔEE technique is used for particle identification and total kinetic energy measurement. We have improved particle separation and installed new detectors that fully stop ions with kinetic energy up to 170 MeV. To reduce the contribution of the low energy tail in the quasi-monoenergetic neutron spectrum, we have applied time-of-flight techniques and investigated the results for measurements with 175 MeV neutrons. We have investigated the response function of the CsI(Tl) scintillators and describe a method for efficiency correction. We have studied the signal-to-background ratio of the new configuration of the spectrometer and of the collimation system. A method to obtain absolute cross-section normalization, separating the peak neutrons from the low-energy tail, is proposed. Finally we have characterized the 175 MeV quasi-monoenergetic neutron spectrum with the Medley spectrometer. This upgraded configuration has been used in 2007 and 2009 for light-ion production measurements at 175 MeV from C, Si, O, Fe, Bi and U. © 2011 Elsevier B.V. All rights reserved.